PERENCANAAN STRATEGIS MULTI SEKTORAL BERBASIS INOVASI TEKNOLOGI ADAPTIF LOKASI (INTAI) SEBAGAI ALTERNATIF PENENTU KEBERHASILAN DESA WISATA - Listyanto, Nurbakti (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
The development of Tourism Village development to date does not yet have a village development concept/model that can be an optimal solution in efforts to eradicate poverty starting from a village. Village development is still carried out on a sectoral basis and does not start with the integration of commodities linked to tourist attractions, thus giving rise to a negative assessment impact on its implementation for success. So that this does not happen, the aim of this study is to provide an opinion based on literature on various multi-cultural aspects in strategic planning through Location Adaptive Technology Innovation (INTAI) which is expected to be the target of the Determining Factors for the Success of a village program in preparing a Concept/Model for a Village Tour. The method used in this writing is qualitative with a descriptive approach which is an effective method in exploring and understanding the meaning originating from social or humanitarian problems in order to produce descriptive data, the analysis technique of which uses an interactive model (Interactive Model of Analysis). From the analysis carried out, to become a Tourism Village, it is hoped that it meets the requirements, some of which are having potential, being unique/distinctive, attractive, accommodating, facilitative, community-based, integrative, able to combine natural tourism, cultural tourism and man-made tourism (technology) in one area, able to activate resource capacity development and business sources, and find branding for the Village by involving all elements and interconnectivity. The conclusion that can be drawn is that the success of the Tourism Village concept is largely determined by determining resources through identification, careful exploration of potential, utilization of aspects and elements of actors in a multi-sectoral, structural and functional manner, being able to integrate and utilize location-adaptive technological innovations.